Plan de mejora del uso de los canales digitales para optimizar la experiencia del cliente y elevar la visibilidad en el mercado de la empresa Mega Alfa Transportes S.A.S del municipio El Cerrito (Valle) (2023)
This document presents a plan to optimize the use of digital channels for Mega Alfa Transportes SAS, with the objective of improving customer satisfaction and increasing visibility in the market. The plan is structured in sections ranging from the presentation of the company to the formulation of objectives, through the analysis of the impact of the lack of digital channels and the creation of a concise infographic. A qualitative and descriptive methodology was employed, supported by desk research and a mixed approach including qualitative and quantitative data.